Temporality and a Metric for Created Natures in Gregory of Nyssa - Lourié, Basil (Scrinium, 2016)
The problem of time in Gregory of Nyssa has been reopened in several recent studies. After a review of these new solutions, the author proposes a more formalised approach taking into account our present knowledge of the logical properties of the infinite sets.